On-Chain Off-Chain Regulation on Crypto Asset in Indonesia Market - Gunawan, Aloysius Bernanda; Tumanggor, M.S.; Rohman, Adi Nur; Syauket, Amalia (Journal of Law, Politic and Humanities, 2025)
The advancement of blockchain technology has created challenges for traditional regulatory frameworks, regarding consumer protection in crypto asset ecosystems. This paper examines dichotomy between on-chain governance mechanisms embedded within blockchain protocols and off-chain regulatory approaches imposed by state authorities. Through normative legal research and comparative analysis of international regulatory practices, this study identifies critical gaps in Indonesia's current crypto asset regulatory framework. The research reveals that existing regulations, through government’s commodity-based approach, inadequately address the technological governance inherent in blockchain systems like smart contracts, decentralized protocols, and automated consensus mechanisms. The study proposes a hybrid regulatory construction that synchronizes technological governance with traditional state regulation to create comprehensive consumer protection. The findings demonstrate that integrating on-chain compliance mechanisms with off-chain oversight can enhance consumer safety while maintaining innovation momentum. This research contributes to digital law study by providing regulatory models suitable for Indonesia's legal system and broader emerging market contexts.